2022
DOI: 10.3390/ani12243452
|View full text |Cite
|
Sign up to set email alerts
|

Management of Enteric Methane Emissions in Ruminants Using Feed Additives: A Review

Abstract: In ruminants’ metabolism, a surplus of hydrogen is removed from the reduction reaction of NAD+ (nicotinamide adenine dinucleotide) by the formation of methane by methanogenic bacteria and archaea methanogens. The balance of calculations between VFA (volatile fatty acids), CO2, and CH4 indicates that acetate and butyrate play a role in methane production, while the formation of propionate maintains hydrogen and therefore reduces methane production. CH4 formation in ruminant livestock is not desired because it r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 104 publications
(113 reference statements)
0
15
0
Order By: Relevance
“…Therefore, the reasons for choosing microalgae as an ingredient or supplement for animal feed are, for instance, their high nutritional value, if cultured under optimal conditions and fed to adapted animals [ 6 ], and their ability to act as feed additives. Particularly, extracted algal bioactive compounds can improve animal production by exerting antimicrobial and immunomodulatory activities [ 7 ] or inhibit methanogenesis in ruminants with positive effects on reducing methane emissions [ 8 , 9 ]. These factors have driven the exploitation of microalgae for human nutrition, animal feed, biofuels, and bioremediation in recent years [ 10 ].…”
Section: Introduction Of Chlorella Vulgarismentioning
confidence: 99%
“…Therefore, the reasons for choosing microalgae as an ingredient or supplement for animal feed are, for instance, their high nutritional value, if cultured under optimal conditions and fed to adapted animals [ 6 ], and their ability to act as feed additives. Particularly, extracted algal bioactive compounds can improve animal production by exerting antimicrobial and immunomodulatory activities [ 7 ] or inhibit methanogenesis in ruminants with positive effects on reducing methane emissions [ 8 , 9 ]. These factors have driven the exploitation of microalgae for human nutrition, animal feed, biofuels, and bioremediation in recent years [ 10 ].…”
Section: Introduction Of Chlorella Vulgarismentioning
confidence: 99%
“…Both in vitro simulation of rumen fermentation and in vivo studies with cows, goats, and sheeps, have been performed with feed incubated in sacco in the rumen or with feeding of biomass from plants rich in PSMs and extracts of varied origins as reviewed in different works 11 , 21 23 . For example, a large in vitro screening study with 450 plant species showed methane-reducing properties of 35 plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this problem, another matter of concern is the livestock methane emissions that have serious implications in the context of global warming and climate change (Johnson and Johnson 1995). Researchers are carrying out studies to understand the methane emissions from livestock and are trying to explore the mitigation strategies that range from management aspects to nutritional interventions (Kumari et al 2020;Palangi and Lackner 2022).…”
Section: Environmental Pollution and Climate Changementioning
confidence: 99%